Development of power system analysis software using object components. - Nor, Khaled Mohamed; Mokhlis, H.; Suyono, Hadi; Abdel-Akher, M.; Abdul Rashid, Abdul Halim; Gani, Taufiq A. (2007)
This paper presents experiences of developing a power system analysis software using a combination of Object Oriented Programming (OOP) and Component Based Development (CBD) methodologies. In this development, various power system analyses are developed into software components. These components are integrated with graphical user interface components to build up a power system analysis application. By using both OOP and CBD methodologies, updating or adding new algorithm can be done to any specific component without affecting other components inside the software. The component also can be replaced with any other better component whenever necessary. Hence, the software can be maintained and updated continuously with minimum resources. The performance of the components is described in comparison with the non-component applications in terms of reuse as well as execution time.